O desencantamento moral da escola pública: um ensaio de compreensão crítica - Gabriel Lelis da Fonseca Ferreira; Carlos Alberto Lopes Sousa (ETD: Educação Temática Digital, 2014)
This essay, which is based upon the perspective of a comprehensive and critical sociology, aims to contribute to the understanding and critique of a recent trend in Brazilian elementary school, herein called “moral disenchantment”. This is a social phenomenon that represents the gradual “reduction of moral diversity” in elementary schools due to a reconfiguration of both the educational demands from the society and the nstitutional offer of schools. Both press for the genesis of a new kind of moral education, whose contours, more or less uniform, reveal traces of a “business ethics”. This ethics tends to conceive of education increasingly as the “delivery of a service” and less as “humanistic formation”. In this essay, particular attention is given to the case of “public school”, which has gradually come to assume certain moral aspects of the so-called “school-enterprise”, in this general movement of homogenization of school moral diversity in Brazil. The analysis of the effects of disenchantment on the public school is carried out in a comparative perspective, given the same effects on other types of school: the “Catholic school” and “military” school”.